Human Capital and Climate Change - Angrist, Noam,Winseck, Kevin,Patrinos, Harry Anthony,Zivin, Joshua S. Graff (National Bureau of Economic Research, 2023)
Addressing climate change requires individual behavior change and voter support for pro-climate policies, yet surprisingly little is known about how to achieve these outcomes. In this paper, we estimate causal effects of additional education on pro-climate outcomes using new compulsory schooling law data across 16 European countries. We analyze effects on pro-climate beliefs, behaviors, policy preferences, and novel data on voting for green parties - a particularly consequential outcome to combat climate change. Results show a year of education increases pro-climate beliefs, behaviors, most policy preferences, and green voting, with voting gains equivalent to a substantial 35% increase
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Bildung; Klimawandel; Humankapital; Wirkungsanalyse; Verbrauchereinstellung; Politische Einstellung; Wahlverhalten; Umweltökonomik; EU-Staaten; Political Processes: Rent-Seeking; Lobbying; Elections; Legislatures; and Voting Behavior; Public Goods; General; Government Policy; Capitalist Institutions; Welfare State; Sustainable Development; Environmental Economics